Clinical and Molecular Heterogeneity of RTEL1 Deficiency - Speckmann, Carsten; Sahoo, Sushree Sangita; Rizzi, Marta; Hirabayashi, Shinsuke; Karow, Axel; Serwas, Nina Kathrin; Hoemberg, Marc; Damatova, Natalja; Schindler, Detlev; Vannier, Jean-Baptiste; Boulton, Simon J.; Pannicke, Ulrich; et al. (Frontiers in Immunology, 2017)
Typical features of dyskeratosis congenita (DC) resulting from excessive telomere shortening include bone marrow failure (BMF), mucosal fragility and pulmonary or liver fibrosis. In more severe cases, immune deficiency and recurring infections can add to disease severity. RTEL1 deficiency has recently been described as a major genetic etiology, but the molecular basis and clinical consequences of RTEL1-associated DC are incompletely characterized. We report our observations in a cohort of six patients: five with novel biallelic RTEL1 mutations p.Trp456Cys, p.Ile425Thr, p.Cys1244ProfsX17, p.Pro884_Gln885ins53X13, and one with novel heterozygous mutation p.Val796AlafsX4. The most unifying features were hypocellular BMF in 6/6 and B-/NK-cell lymphopenia in 5/6 patients. In addition, 3 patients with homozygous mutations p.Trp456Cys and p.Ile425Thr also suffered from immunodeficiency, cerebellar hypoplasia and enteropathy, consistent with Hoyeraal-Hreidarsson syndrome. Chromosomal breakage resembling a homologous recombination defect was detected in patient-derived fibroblasts but not in hematopoietic compartment. Notably, in both cellular compartments differential expression of 1243aa and 1219/1300aa RTEL1 isoforms was observed. In fibroblasts response to ionizing irradiation and non-homologous end joining were not impaired. Telomeric circles did not accumulate in patient-derived primary cells and lymphoblastoid cell lines, implying alternative pathomechanisms for telomeric loss. Overall, RTEL1-deficient cells exhibited a phenotype of replicative exhaustion, spontaneous apoptosis and senescence. Specifically, CD34+ cells failed to expand in vitro, B-cell development was compromised, and T-cells did not proliferate in long-term culture. Finally, we report on the natural history and outcome of our patients. While two patients died from infections, hematopoietic stem cell transplantation (HSCT) resulted in sustained engraftment in two patients. Whether chemotherapy negatively impacts on the course and onset of other DC-related symptoms remains open at present. Early onset lung disease occurred in one of our patient after HSCT. In conclusion, RTEL deficiency can show a heterogeneous clinical picture ranging from mild hypocellular BMF with B/NK cell lymphopenia to early-onset, very severe and rapidly progressing cellular deficiency.